Emotional intelligence, employee adaptability and job satisfaction: evidence from hospitality industry in vietnam - Phạm. Thị Hoài Giang (2020)
This study examines relationships between emotional intelligence, employee adaptability and job satisfaction in the context of hospitality industry in Vietnam. Specifically, the research focuses on impact of emotional regulation on job satisfaction and mechanism through which inter-personal adaptability and service offering adaptability mediate the relationship between emotional regulation and job satisfaction. Design/Methodology/Approach: The questionnaire survey is employed to collect data from 164 respondents from hospitality in Vietnam. The data were analyzed by Partial Least Square-Structural Equation Modelling (Smart PLS 3.2.8).